1999
DOI: 10.1002/(sici)1097-0215(19990730)82:3<435::aid-ijc18>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid: A new cytotoxic agent against malignant brain-tumor cells

Abstract: Malignant brain tumors are the most common solid tumors in children. The overall prognosis for this group of patients is still poor, emphasizing the importance of more effective therapies. Betulinic acid (Bet A) has been described as a novel cytotoxic compound active against melanoma and neuroblastoma cells. Here we report that Bet A was active against medulloblastoma and glioblastoma cell lines. In addition, Bet A exerted cytotoxic activity against primary tumor cells cultured from patients in 4 of 4 medullob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 24 publications
11
132
0
5
Order By: Relevance
“…Other pentacyclic triterpenes such as oleanane and ursane could not differentiate B16 2F2 cells. Previously, it was reported that compound 10 was a selective anticancer agent against some human cancer cell lines (Fulda et al 1999;Pisha et al 1995;Schmidt et al 1997), and the carboxyl group at the C-17 was essential for apoptotic activities (Lee et al 1998). In our studies of anti-proliferative effects by these triterpenes on B16 2F2 cells, compounds 8-12, all of which have a carbonyl group at C-17, were found to inhibit B16 2F2 cell proliferation at lower concentrations than other compounds.…”
Section: Structure-activity Relationships Of Melanogenesis and Apoptomentioning
confidence: 61%
“…Other pentacyclic triterpenes such as oleanane and ursane could not differentiate B16 2F2 cells. Previously, it was reported that compound 10 was a selective anticancer agent against some human cancer cell lines (Fulda et al 1999;Pisha et al 1995;Schmidt et al 1997), and the carboxyl group at the C-17 was essential for apoptotic activities (Lee et al 1998). In our studies of anti-proliferative effects by these triterpenes on B16 2F2 cells, compounds 8-12, all of which have a carbonyl group at C-17, were found to inhibit B16 2F2 cell proliferation at lower concentrations than other compounds.…”
Section: Structure-activity Relationships Of Melanogenesis and Apoptomentioning
confidence: 61%
“…Betulinic acid (BetA) is a naturally occurring pentacyclic triterpenoid derived from white birch trees, which has been shown to induce apoptosis in a variety of tumor cells (Pisha et al, 1995;Fulda et al, 1997Fulda et al, , 1999Zuco et al, 2002) We previously described that BetAinduced apoptosis differs from that induced by anticancer agents such as doxorubicin, since BetA-induced apoptosis is not associated with the activation of ligand/ receptor systems, such as CD95, and does not involve p53 (Fulda et al, 1997). In BetA-induced apoptosis, perturbation of mitochondrial function, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Tel que décrit dans les nombreuses revues de littérature publiées à ce sujet [Hayek et al, 1989; Baglin et al, 2003a; Patocka, 2003;Setzer et al, 2003;Ovesnâ et al, 2004;Bi et al, 2005; Sami et al, 2005; Mukherjee et al, 2006;Tolstikova et al, 2006a; Tolstikova et al, 2006b; Sporn et al, 2007], l'acide bétulinique (15) [Schmidt et al, 1997;Fulda et al, 1999;Fulda et al, 2000;Jung et al, 2007;. Noda et ses collaborateurs [1997] [Schmidt et al, 1997;Fulda et al, 1999; Wick et al, 1999;Fulda et al, 2000;Fulda et al, 2005; Galgon et al, 2005]. Soler et al, 1996; Sun et al, 1998; Sun et al, 2002;Huang et al, 2006;Yu et al, 2006].…”
Section: Activités Biologiquesunclassified
“…Des études subséquentes ont révélé que le potentiel anticancéreux de l'acide bétulinique (15) pouvait être étendu à d'autres types de lignées cellulaires dérivées des types de cancer les plus prévalents dans la population humaine (poumon, côlon, sein, prostate, cerveau, etc.) [Schmidt et al, 1997;Fulda et al, 1999;Fulda et al, 2000;Jung et al, 2007;. Noda et ses collaborateurs [1997] À cet effet, l'étude in vivo de Pisha et al [1995] sur souris porteuses de tumeurs murines a révélé que le traitement avec l'acide bétulinique (15) n'induisait aucune toxicité, métastases ou anormaîités structurales chez les organes vitaux des souris.…”
Section: Activités Biologiquesunclassified